AB0753 Arterial stiffness increase in the early phase of arthropathy related with psoriatic arthritis is not further modified by stable prolonged retention of a minimal disease activity condition. (15th June 2017) - Fischetti, F; Bozzao, F; Rovina, M; Simon, G; Bardelli, M; Carretta, R
Abstract : Background: Increased large arteries wall stiffness (AS) is a well known independent morbidity and mortality cardiovascular risk factor, not only related to hypertension and diabetets, but also induced by long standing systemic inflammation, as observed in inflammatory rheumatic or gut chronic diseases. Psoriatic arthritis (PsA) was also shown to increase cadiovascular morbidity, but this observation was commonly related with the associated occurrence of long term arthritis, disease activity and CV traditional risk factors Objectives: To assess whether in a selected group of PsA patients, affected by recent onset (4–12 months) arthritis, not suffering from CV disease risk factors, evidence could be obtained of an early alteration of arterial wall function as expressed by an increased arterial pulse wave velocity (aPWV) and secondary reduced tonometric subendocardial viability ratio (tSEVR). Further, we evaluated if a 18 months (Mth) treatment with synthetic disease modifying antirheumatic drugs (sDMARD) other than cyclosporine, leading to a demonstrable target of clinical "minimal disease activity"(MDA) could modify such possible modifications Methods: Conclusive data were obtained in a selected goup of 12 PsA patients (Pts) (CASPAR criteria classified) (M/F, 6/5; mean age, 50.8; range, 40–65) not suffering from axial spondylitis who firsly underwent (without any previous treatment) aPWV measurement (PulsePen, Diatecne Srl, Milan) and tSEVR calculation, and then were re-evaluated for the same calculations after a 18 Mth time of sDMARD treatment. Each of the PsA Pts had a 3–4 Mth follow up and showed to reach the target of stable MDA (with also ultrasound confirmed remission of active synovitis) after a 4–8 Mth treatment. Before treatment, the group of PsA Pts was compared with an age, body weight, CV parameters and risk factors–matched control group of voluntary 22 healthy subjects (M/F, 11/11; mean age, 51.3; range, 41–67) Results: Before any treatment, aPWV was higher in the group of patients with PsA than in control subjects (median, 8.667 m/s vs 6.963 m/s, p<0.02) while tSEVR was decreased (median, 1.44 vs 1.50, p<0.05). Aortic PWV was not modified after the sDMARD treatment (median m/s, before=8.691, after=8.048, p=0.55), despite statistically significant improvements of the disease activity scores (DAS28; modified CPDAI; DAPSA) as well as cutaneous PASI, and stable retention of a MDA condition. A direct correlation (Spearman rank) between aPWV and DAS28 (rho=0, 70; p-value=0, 04), BASDAI (rho=0, 77; p-value=0, 01), and HAQ (rho=0, 66; p-value=0, 05) was found, not instead between aPWV and ESR or CRP. Pts with PsA, at the end of the follow up, had increased levels of systolic (134, 1±14, 3 vs 122±11, 2, p<0, 05) and diastolic (82±7, 4 vs 73, 5±6, 6, p<0, 05) blood pressure, with unmodified heart rate Conclusions: Early onset of PsA seems to be associated with already established and stable increase of AS. Subclinical previous phase of inflammation and length of psoriatic disease could be addressed as possible causes Disclosure of Interest: None declared